Developing a Genetic Linkage Map from an Intervarietal Cross of Serotypes A and D and the Analysis of the Costs and Benefits of Hybridization in Cryptococcus neoformans - Han, Xiaoyu (My University, 2004)
N/A
Hybridation in Cryptococcus neoformans
Keywords: genetic; linkage; map; serotype; benefit; hybridization; cryptococcus; cryptococcus neoformans